calculus
posted by hi .
Hey I am working on differentiation/quotient rule for this problem...can someone help me?
x^23/x2.

if y=u/v,
y' = (u'vuv')/v^2
so, let u = x^23, u'=2x
let v = x2, v'=1
y' = ((2x)(x2)(x^23)(1))/(x2)^2
= (2x^22xx^2+3)/(x2)^2
= (x^24x+3)/(x2)^2
= (x3)(x1)/(x2)^2
or, you can always think of it as a product rule:
y = (x^23) * (x2)^1
y' = (2x3)/(x2)  (x^23)*(x2)^2
which works out the same
Respond to this Question
Similar Questions

Math  Calculus Question.
hey can someone explain to me the relationship between the chain rule and implicit differentiation? 
Calculus
I need to find the derivative of the following problem via logarithmic differentiation, but I'm getting stuck. I know how to solve via logarithmic differentiation, but I can't figure out how to rewrite the exponent(s) as logs. Could … 
Calculus
Let f(x)= 5x  x–2 are we supposed to use the quotient rule? 
Calculus
f(x)=5+(6/x)+(7/x^2), find f'(x). I haven't done fractions without using the quotient rule im not so sure this would work with quotient rule what do i do? 
Calculus
How do I use the chain rule to find the derivative of square root(1x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used? 
calculus
Alright so implicit differentiation is just not working out for me. Use implicit differentiation to find the slope of the tangent line to the curve at point (4,1). y / (x2y) = x^3 + 4 Tried quotient rule to get the derivative of the … 
Implicit Differentiation
Use implicit differentiation to find the slope of the tangent line to the curve y/x+6y=x^2–6 at the point (1,–5/31) . Again i think i'm messing up with the algebra here. I used quotient rule to get [(x+6y)(y')(y)(1+6y')]/(x+6y)^2=2x … 
Calculus
How do you use imlicit differentiation to differentiate e^(xy)? 
Calculus
1.) Find the derivative of tan (sec x). 2.) Find the derivative if 1/x in four ways, using the limit process, power rule, quotient rule and implicit differentiation. 3.) Show that the derivative of sec^1 x is 1/(x*sqrt(x^2 1)). … 
Calculus
Quotient Rule: Use the limit definition of the derivative to prove that the quotient rule